Strategi Bertahan Pedagang Pasca Bencana Kebakaran di Pasar Atas Kota Bukittinggi - Fadilla Amalia Putri (Jurnal Sosiologi Andalas, 2019)
Abstract: Fires that occurred in the Upper Market of the City of Bukittinggi resulted in traders being moved totrade in the shelter market. This requires him to be able to survive and deal with the obstacles that are presentwhen starting to trade again in the shelter market. The purpose of this study is to describe the forms of survivalstrategies undertaken by traders and the obstacles faced by traders in surviving post-fire disasters. Thisresearch was analyzed using social action theory (rational instrumental) proposed by Max Weber. Thisresearch uses a qualitative approach with descriptive type. To obtain relevant data and information inaccordance with the objectives of the study, researchers had interviewed 16 informants. The results of thisstudy indicate that there are 3 forms of strategies carried out by traders in surviving post-fire disasters, thefirst strategy is the active strategy, a strategy carried out by utilizing all the potential possessed by traders, thesecond strategy is a passive strategy, namely a strategy by minimizing expenditure , and the last strategy is,network strategy, which is a strategy carried out by utilizing the social network of traders. Constraints faced bytrading again in the shelter market in the form of unsettled shelter market conditions for both buyers andtraders, lack of information provided about the existence of the shelter market.